Der Zweite Weltkrieg in postsozialistischen Gedenkmuseen Geschichtspolitik zwischen der ,Anrufung Europas' und dem Fokus auf ,unser' Leid - Radonić, Ljiljana (Medien und kulturelle Erinnerung, 2021)
This volume is the first to examine the museum landscape of all post-socialist EU member states. How do museums present the Second World War, the Holocaust, and Soviet crimes? As part of their nations' attempts to join the EU, some "invoke" Europe, aiming to prove their Europeanness by adopting international museification trends. Others demand that "Europe" recognizes their suffering under Soviet rule as the greater evil.